Head cases : a novel [large type] - McMahon, John, 1970- (Thorndike Press large print thriller, adventure and suspense., 2025)
"Gardner Camden is a walking analytical brain with an affinity for riddles, puzzles, and codes. It makes him the perfect fit for the Patterns and Recognition (PAR) unit of the FBI, a team of five brilliant but misfit agents tasked with solving cold cases. Gardner's smart, but he's all business--except for his seven-year-old daughter and occasional visits to his elderly mother, he prioritizes his work and justice over everything else, no matter the cost. With rumors of PAR about to be disbanded, the team can't afford to make any mistakes. A serial killer from one of Gardner's solved cases, presumed to be dead for over a decade, is found murdered, and then soon after, another body with a similar story. The mastermind murderer has left clues and riddles for Gardner and his team--a mathematician, a sniper and weapons expert, a computer analytics specialist, and their leader, a career agent--as they track him across the country. With the threat of PAR dissolving, Gardner must work to solve the riddles before it's too late."--